PENGARUH ANALISIS LAPORAN ARUS KAS OPERASI, ARUS KAS INVESTASI , TERHADAP HARGA SAHAM PERUSAHAAN ELEKTRONIK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 2018-2021 - Hevin Rivaldo Gulo; Kristi Endah Ndilosa Ginting (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2023)
Indonesia's economic development from year to year will continue to grow. This is marked by the establishment of many companies, both state-owned companies and foreign companies. With so many companies operating in Indonesia, it will certainly promote a level of competitive business competition by business operators so that companies need various plans so that they can always survive in the world of business competition and compete to become market leaders in every field of the same business. Report operating cash flows that are directly related to the operational activities involved in determining net income for a given period. These activities are obtained from the company's revenue relating to transactions that affect profit or loss. Cash Flow Report is a type of financial statement that presents the company's cash flow from operating activities, investment, there are 2 samples of companies listed on the IDX, companies that have the code ATIC in 2020-2021, there has been an increase in cash flow from operating activities by 16.22% and there was an increase in earnings per share of 15.63% but the share price decreased by 1.88% therefore the company was in trouble. Likewise with companies that have PTSN codes in 2019-2020 there was a decrease in cash flow from investing activities of 114.86% but there was an increase in share price of 39.71%, therefore the company was in trouble.